Unlocking the Potential of Information Communications Technology to Improve Water and Sanitation Services : Summary of Findings and Recommendations - Ndaw, Mouhamed Fadel (World Bank, Washington, DC, 2017)
Information Communications Technology (ICT) growth and adoption is changing the landscape of developing countries. Initial applications are showing how ICTs can further water, sanitation, and hygiene (WASH) goals and priorities, including increasing access, improving service delivery and improving governance. This study aims to take stock and reflect on the findings from key ICT applications and experiences both in other sectors as well as in the WASH sector itself. By documenting and analyzing past successes, failures, enablers and barriers of the key applications and experiences, it is possible to significantly advance the areas of policy development, guidelines, implementation, and scale up of ICT in the WASH sector. The specific objectives of the study were to: (a) take stock of emerging uses of ICT across sectors including agriculture, health, education and governance; (b) document the relevant experiences of key ICT applications (both failures and good practices) in the water and sanitation sector globally and in selected African countries; (c) identify binding constraints impacting ICT adoption and scale-up as well as the role of different actors (private, public, development community, civil society, etc.); (d) develop policy and guidelines for the at-scale use of ICTs in the water and sanitation sector, including opportunities for public/private partnerships; and (e) facilitate country peer-to-peer exchanges and regional learning network.